Additive manufacturing: direct-energy-deposition process parameters optimisation via experiments (A) - Pey, Zhi Kai (Nanyang Technological University, 2024)
This research explores the influence of Direct Energy Deposition (DED) process parameters on the microstructure of 316L stainless steel, specifically examining how changes in laser power, scanning speed, powder mass flow rate, and incremental ratios affect grain characteristics. Utilizing Electron Backscatter Diffraction (EBSD) for detailed analysis, this study investigates the relationship between these process settings and key microstructural features such as grain size, orientation, and boundaries, which are crucial for determining the steel's mechanical properties. The results reveal that finer grain structures, attributed to optimized DED parameters, significantly enhance mechanical properties through the Hall-Petch effect, where increased grain boundaries act as barriers to dislocation movement, thus improving strength and hardness. Additionally, the grain orientation analysis provided insights into the material’s anisotropy, impacting its toughness and ductility depending on the loading direction. These findings highlight the potential of DED to tailor materials for specific mechanical requirements. In Conclusion, this study not only deepens the understanding of the DED process of microstructural control but also offers practical guidance for optimizing DED settings to achieve desired material properties. This is particularly valuable for industries like aerospace and healthcare, where material performance is critical. Future research should focus on real-time monitoring of these microstructural changes and exploring post-processing treatments to enhance material properties.